Systematic Review and Meta-Analysis of Randomized Controlled Studies on the Fuke Qianjin Capsule - Lu, Si-Qi; Han, Qian-Xi; Xu, Long-Chen; Zhou, Ping-Da; Zhou, Jia-Meng; Wang, Wei; Pan, Jie; Zhu, Wen-Tao (Current Traditional Medicine, 2025)
ObjectiveThis research aims to evaluate the efficacy and safety of the Fuke Qianjin capsule combined with antibiotics in the treatment of chronic pelvic inflammatory disease, including the associated complications (endometritis and adnexitis).MethodologyWe searched 4 Chinese and 3 English databases from their establishment to May, 2023. A randomized controlled trial (RCT) of the Fuke Qianjin capsule combined with antibiotics was included in the trial group. The meta-analysis used the RevMan 5.4 software provided by the Cochrane collaboration network.ResultsA total of 103 RCTs were included, specifically 58 on chronic pelvic inflammatory disease, 6 on endometritis, and 39 on adnexitis (n= 9820, trial group n = 4925, control group n = 4895). The results of the meta-analysis demonstrated that the total effective rate of the Fuke Qianjin capsule combined with antibiotics in the treatment of chronic pelvic inflammatory disease (RR=1.21, 95%CI [1.18, 1.25], Z=14.86, p < 0.00001), endometritis (RR=1.22, 95%CI [1.13, 1.31], Z=5.31, p < 0.00001), and adnexitis (RR=1.26, 95%CI [1.23, 1.30], Z=16.49, p < 0.00001) was significantly better than that of antibiotics alone. Equally important, the relief time of clinical symptoms, the incidence of adverse reactions, and the recurrence rate (p < 0.05) were significantly lower than those of antibiotics alone.ConclusionThe Fuke Qianjin capsule combined with antibiotics was found to be superior to those in the antibiotic group alone. However, this conclusion necessitates further improvements, such as being supported by a greater number of high-quality and substantive research samples.
Keywords: endometritis and adnexitis